Heavy Metal Contamination of Water, Soil and Vegetables in Urban Streams in Machakos Municipality, Kenya - Tomno, Rose M; Nzeve, Julius K; Mailu, Stephen N; Shitanda, Douglas; Waswa, Fuchaka (Elsevier, 2020)
Pollution of the environment by heavy metals emanating from rapid economic growth and improper waste and effluent disposal is a major concern. In this study, heavy metal concentrations (Cd, Cu, Pb, Zn and Cr) in vegetables, soil and water in two urban streams in Machakos municipality were analyzed. Physicochemical parameters; pH, temperature, total dissolved solids (TDS) and electrical conductivity (EC) were also measured on-site. One-way Analysis of variance (ANOVA) was used to test for the significant difference (p≤0.05) of heavy metal concentrations in the vegetables, soil, and water across the different sampling sites. The relationship between the heavy metals in the soil, water and vegetables was investigated using Pearson correlation. Temperature (21.58 – 23.05 ºC), pH (7.5 – 8.45) and TDS (577.5 – 865.83 mg/L) mean values were found to be within WHO acceptable limits for surface water while EC (864 – 1778.5 µS/cm) exceeded the set limits. Results showed that the mean concentrations (mg/kg) of Cd (BDL – 0.0011), Cu (0.0034 – 0.0055), Pb (0.0012 – 0.007), Zn (0.0232 - 0.1351), and Cr (0.0036 - 0.0292) in water and Cd (0.0058 - 0.0534), Cu (10.39 – 27.5), Pb (4.23 - 8.35), Zn (20.1 – 28.8) and Cr (8.17 – 10.03) in soil were within WHO permissible limits. Mean concentration values of (Zn (9.05 – 11.8), Pb (0.28 – 0.636), Cr (BDL – 1.002)) in spinach exceeded WHO permissible limits while Cd (BDL – 0.1285) and Cu (3.07 – 14.5) were within recommended levels. Cd (0.004 – 0.243), Cu (0.909 – 3.60) and Pb (BDL – 0.458) concentration levels in kale were within WHO safe limits for human consumption while Zn (12.06 – 18.8) and Cr (BDL – 1.62) exceeded WHO set limits. Presence of heavy metals (Zn, Pb, Cr) in the vegetables signifies a health risk hazard from consumption of these vegetables. Continuous monitoring of heavy metals in stream water, soil and vegetables is critical towards safeguarding public health
Keywords: Heavy metals; urban effluent; water; soil; vegetables